Molecularly defined sinonasal malignancies: an overview with focus on the current WHO classification and recently described provisional entities - Skálová, Alena; Agaimy, Abbas; Bradova, Martina; Poorten, Vincent Vander; Hanna, Ehab; Guntinas-Lichius, Orlando; Franchi, Alessandro; Hellquist, Henrik; Simpson, Roderick H W; Lopéz, Fernando; Nuyts, Sandra; Chiesa-Estomba, Carlos; et al. (Virchows Archiv, 2024)
Classification of tumors of the head and neck has evolved in recent decades including a widespread application of molecular testing in tumors of the sinonasal tract, salivary glands, and soft tissues with a predilection for the head and neck. The availability of new molecular techniques has allowed for the definition of multiple novel tumor types unique to head and neck sites. Moreover, an expanding spectrum of immunohistochemical markers specific to genetic alterations facilitates rapid identification of diagnostic molecular abnormalities. As such, it is currently possible for head and neck pathologists to benefit from a molecularly defined tumor classification while making diagnoses that are still based largely on histopathology and immunohistochemistry. This review covers the principal molecular alterations in sinonasal malignancies, such as alterations in DEK, AFF2, NUTM1, IDH1-2, and SWI/SNF genes in particular, that are important from a practical standpoint for diagnosis, prognosis, and prediction of response to treatment.
Keywords: nádory vedlejších dutin nosních; Biomarkers, Tumor; Sinonasal; Soft tissue; Head and neck; Molecular diagnostics; lidé; Světová zdravotnická organizace; nádorové biomarkery; Humans; World Health Organization; Sinonasal tumor; Paranasal Sinus Neoplasms; Next-generation sequencing